Development of Spicy Cookies By Adding Jamun Seed Powder (International Journal of Food and Nutritional Sciences, 2025)
The study of spicy cookies was developed by using wheat flour, jamun seed powder, butter, Whole milk, chili powder, turmeric powder, cumin seed, curry leaves ,coriander leaves, salt, Baking soda , Baking powder to the improve the quality and quantity of spicy cookies. In Spicy Cookies preparation different levels of jamun seed powder and wheat flour used for making delicious spicy cookies with maximum amount of protein, fiber, Vitamin, minerals and carbohydrates. Finally selected T2 or 10% jamun seed powder of spicy cookie onthe basis of higher score of sensory evaluation such as color, texture, flavor, overall acceptability. The final spicy cookiescontain1.74%moisture,2.69% ash,8.45%protein,4.51%crudefiber,7.93% fat,77.82% carbohydrates,6.24 % minerals & 416.46% total energy. Spicy cookies shelf life was 60days on the basis of the microbial study, From61 days ,microbial result count increases fromout of the range. Finally Spicy cookies shelf life was 60days safely as per our study. Spicy cookies can be recommended to the diabetic patient. No any sugar or jaggary added in spicy cookies hence it is good for children’s, adult and diabetic patients.